Desarrollo de aplicación piloto para análisis comparativo en la adquisición de nueva tecnología en el hospital Universitario Mayor Méderi (2020)
Biomedical equipment is vitally important tools in a health care institution such as Méderi, they have a period of time during which they can be marketed and used; this period of time is known as the useful life of the equipment. For this reason, when medical devices end this period, it is necessary to deregister the device and purchase a new equipment. This work shows the development of a tool in Excel that allows a qualitative comparison of biomedical equipment, specifically the Vital Signs Monitor and the anesthesia machine.